The biogenic content of process streams from mechanical-biological treatment plants producing solid recovered fuel. Do the manual sorting and selective dissolution determination methods correlate? - Severin, M.; Velis, C. A.; Longhurst, Philip J.; Pollard, Simon J. T. (Elsevier Science B.V., Amsterdam., 2010)
The carbon emissions trading market has created a need for standard methods for the determination of biogenic content (chi(B)) in solid recovered fuels (SRF). We compare the manual sorting (MSM) and selective dissolution methods (SDM), as amended by recent research, for a range of process streams from a mechanical biological treatment (MBT) plant. The two methods provide statistically different biogenic content values, as expressed on a dry mass basis, uncorrected for ash content. However, they correlate well (r(2) > 0.9) and the relative difference between them was <5% for chi(B) between 21% (w)/W-d and 72% (w)/W-d (uncorrected for ash content). This range includes the average SRF biogenic content of ca. 68% (w)/W-d. Methodological improvements are discussed in light of recent studies. The repeatability of the SDM is characterised by relative standard deviations on triplicates of <2.5% for the studied population. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: waste fossil